Production of the Plant Hormone Auxin by Salmonella and Its Role in the Interactions with Plants and Animals - Cox, Clayton E.; Brandl, Maria T.; de Moraes, Marcos H.; Gunasekera, Sarath; Teplitski, Max (Frontiers in Microbiology, 2018)
The ability of human enteric pathogens to colonize plants and use them as alternate hosts is now well established. Salmonella, similarly to phytobacteria, appears to be capable of producing the plant hormone auxin via an indole-3-pyruvate decarboxylase (IpdC), a key enzyme of the IPyA pathway. A deletion of the Salmonella ipdC significantly reduced auxin synthesis in laboratory culture. The Salmonella ipdC gene was expressed on root surfaces of Medicago truncatula. M. truncatula auxin-responsive GH3::GUS reporter was activated by the wild type Salmonella, and not but the ipdC mutant, implying that the bacterially produced IAA (Indole Acetic Acid) was detected by the seedlings. Seedling infections with the wild type Salmonella caused an increase in secondary root formation, which was not observed in the ipdC mutant. The wild type Salmonella cells were detected as aggregates at the sites of lateral root emergence, whereas the ipdC mutant cells were evenly distributed in the rhizosphere. However, both strains appeared to colonize seedlings well in growth pouch experiments. The ipdC mutant was also less virulent in a murine model of infection. When mice were infected by oral gavage, the ipdC mutant was as proficient as the wild type strain in colonization of the intestine, but it was defective in the ability to cross the intestinal barrier. Fewer cells of the ipdC mutant, compared with the wild type strain, were detected in Peyer’s patches, spleen and in the liver. Orthologs of ipdC are found in all Salmonella genomes and are distributed among many animal pathogens and plant-associated bacteria of the Enterobacteriaceae, suggesting a broad ecological role of the IpdC-catalyzed pathway.